Modifikasi Sistem Kontrol Motor Listrik Menggunakan Inverter dengan Distance Sensor Pada Alat Penggulung Side Gume. - Susilawati, Dera; Dharmanto; Kahlil Firdausi, Muhammad; Aldisar Syarifudin, Ahmad (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2025)
The high level of scrap in the bias cutting process at PT. ADM, particularly caused by ineffective side gume rolling, has impacted production efficiency. This final project aims to overcome this issue by modifying the side gume roller system on the DBC-03 machine. The original pneumatic motor was replaced with a three-phase induction motor, controlled by a PLC system integrated with a distance sensor and inverter to automatically adjust motor speed based on the diameter of the rolled material. The modification process included designing, assembling, and implementing the control system, followed by field testing. The results show that the new system significantly improves the roller's pulling strength, increases the rolling capacity, and enhances ease of operation. The distance sensor accurately detects changes in material diameter, and the inverter ensures stable speed control. Overall, the modified system has proven effective in reducing scrap, supporting continuous production, and providing a reliable solution for the bias cutting process in the tire manufacturing industry.